2015
DOI: 10.1242/jeb.122283
|View full text |Cite
|
Sign up to set email alerts
|

Tight coordination of aerial flight maneuvers and sonar call production in insectivorous bats

Abstract: Echolocating bats face the challenge of coordinating flight kinematics with the production of echolocation signals used to guide navigation. Previous studies of bat flight have focused on kinematics of fruit and nectar-feeding bats, often in wind tunnels with limited maneuvering, and without analysis of echolocation behavior. In this study, we engaged insectivorous big brown bats in a task requiring simultaneous turning and climbing flight, and used synchronized high-speed motion-tracking cameras and audio rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 49 publications
(66 reference statements)
0
13
1
Order By: Relevance
“…Nose and nostril morphology are also influenced by respiratory and thermoregulatory demands [77], though how these demands interact with sniffing and olfaction is still unclear. In bats, the respiratory cycle is closely related to the wing-beat cycle, and echolocation pulses are generally emitted during expiration [83][84][85]. Sniffing, or bouts of increased air intake, is often associated with exposure to olfactory stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…Nose and nostril morphology are also influenced by respiratory and thermoregulatory demands [77], though how these demands interact with sniffing and olfaction is still unclear. In bats, the respiratory cycle is closely related to the wing-beat cycle, and echolocation pulses are generally emitted during expiration [83][84][85]. Sniffing, or bouts of increased air intake, is often associated with exposure to olfactory stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…Echoic navigation was obvious when the bats flew ( Figure 5.2), presumably being used to avoid the fly mesh walls (Falk et al, 2015), but is in contrast to previous accounts on N. gouldi in the laboratory, where bats flew in silence . The presence of echolocation during encounters with silent prey may also simply reflect detection of the background (arena walls or floor).…”
Section: Acoustic Strategies Of Terrestrial Predation By Nyctophiluscontrasting
confidence: 88%
“…Bats dynamically adjust PD to avoid the overlap between incoming echoes and the outgoing sonar call. In addition, bats can also adjust the PI of sonar calls to avoid ambiguity of echo assignment over successive calls (Moss and Surlykke, 2001;Schnitzler and Kalko, 2001;Wilson and Moss, 2004;Falk et al, 2015). In our study, only the predictability of target motion was manipulated across trials and days.…”
Section: Temporal Patterning Of Sonar Sounds May Sharpen Localizationmentioning
confidence: 99%
“…Insectivorous bats reduce the interval between sonar calls as the distance to prey decreases Kalko and Schnitzler, 1989;Moss and Surlykke, 2001), and embedded in foraging call sequences are sonar sound groups (SSGs), which are defined as clusters of echolocation signals at comparatively short and stable pulse intervals, flanked by signals at longer intervals (Moss and Surlykke, 2001;Moss et al, 2006;Kothari et al, 2014). The production of SSGs is an adaptive sonar behavior that has been reported in both laboratory and field studies of bat echolocation, in free-flying animals (Surlykke and Moss, 2000;Moss and Surlykke, 2001;Moss et al, 2006;Petrites et al, 2009;Kothari et al, 2014;Sändig et al, 2014;Falk et al, 2015;Wheeler et al, 2016) and those tracking moving prey from a stationary position (Aytekin et al, 2010;Kothari et al, 2014). Past studies have shown that bats temporally cluster echolocation calls to produce SSGs when they are engaged in tasks that require higher spatiotemporal resolution.…”
Section: Introductionmentioning
confidence: 99%